Relação entre os achados histopatológicos da biópsia do enxerto e disfunção hepática após transplante - Silva Filho, José Francisco Rêgo e (2022)
The hepatic insufficiency of the graft is one of the most feared complications after liver transplantation. It threatens the recipient's life and, in acute cases in which causes for such failure are not identified, such as hepatic artery or portal vein thrombosis or heart failure, it is called a Primary Graft Dysfunction or Primary Nonfunction. There are several risk fac-tors for graft failure and hepatic steatosis is considered one of the main ones. The lack of grafts in most countries, including ours, and the high mortality on the transplant waiting list, force us to use organs from expanded criteria donors, including livers with macrovesi-cular steatosis. The objective of this study was to compare rates of Primary Graft Dysfunc-tion or Primary Nonfunction, in addition to re-transplantation and mortality, when using organs with different degrees of steatosis and other microscopic alterations, evidenced in biopsy of the grafts performed during harvesting surgery. Data were collected from 385 patients who underwent liver transplantation from January 2015 to December 2018. The incidence of re-transplantation was 2.33% and the mortality of liver transplantation in 30 days was 6.49%. It was evidenced that grafts without macrovesicular steatosis had a pro-tective factor for dysfunction, developed in 40.8% of grafts, while grafts with severe stea-tosis (more than 60%) had a higher probability of progression to dysfunction (90.9%). There was no statistical difference regarding the evolution to Primary Graft Dysfunction or Primary Nonfunction according to the degree of microvesicular steatosis, ballooning or hepatic fibrosis. In conclusion, the presence of severe macrovesicular steatosis was the only factor associated with primary graft dysfunction.